Anal mucosal melanoma presenting as per rectal bleed: a case report - Bhosale, Aditya M.; Shrotriya, Siddhant; Naik, Suresh; Kulkarni, Bahar (International Journal of Research in Medical Sciences, 2024)
Anorectal mucosal melanoma is a rare, malignant and aggressive tumor that usually presents late. It primarily arises from the melanocytes but can also arise from the mucosal surface. It also carries poor survival rates. Early diagnosis of the disease and prompt treatment is necessary. Overall 5-year survival rate for anal melanoma is below 10%. We present a case of a 77 years old male patient who presented with chief complaints of per rectal bleeding and decreased appetite. Patient’s symptoms were initially confused for benign conditions like hemorrhoids. He was diagnosed with anal mucosal melanoma on per rectal biopsy. Patient’s radiological investigations including PET scan and MRCP were suggestive of liver and lung metastasis. In view of the advanced stage of the disease, the decision was taken to treat the patient conservatively. He was started on imatinib therapy and a regular follow up was kept and palliative care was provided.